Assessment of milk and blood enzymes in Holstein cows with subclinical mastitis - Shimaa Ghanem Yehia; Mena Fouad Saad; Tarek Elsayed Mosallam (Mljekarstvo)
The objective of this study was to determine the activities of lactate dehydrogenase (LDH), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in the milk and blood of lactating Holstein cows and investigate their association with subclinical mastitis (SCM). This study also aims to evaluate the impact of SCM and its severity based on California mastitis test (CMT) scores on the above mentioned enzymes, as well as to test the efficiency of their use as an early predictive diagnostic tool. Thirty multiparous, lactating dairy Holstein cows were examined using CMT and according to the obtained results classified into four groups; control group 1 (SCM-free = 10, score = 0), group 2 (weak positive = 8, score +1), group 3 (positive = 7, score +2) and group 4 (strong positive = 5, score +3). The milk LDH, ALP, and GGT activities were significantly higher in groups 3 and 4 compared to group 2 and the control group. LDH activity was significantly higher in group 2 compared to the control group. The mean blood LDH and ALP activities in SCM groups were significantly higher than in the control group. ALP blood activity was significantly higher in group 4 compared to group 2. The blood GGT activity was significantly higher in group 4 compared to other groups. There was a significant positive association between milk LDH, ALP, and GGT enzymes as well as the blood enzymes (ALP and GGT) in SCM cows. The results showed that subclinical mastitis causes considerable changes in the activities of enzymes in milk and blood of infected cows.